Why Does Generation Z Love Using Apple Products as Personal Branding on Their Social Media? - Gavriella Godeliva; Ni Made Ras Amanda Gelgel (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
Young people, particularly members of Generation Z, are the technological generations. They are always on the cutting edge of technology. Apple is one of the technology brands with generationally positive sentiment. This generation uses Apple products not only for technical reasons but also as a form of personal branding. They frequently upload photos taken with an Apple device to their social media accounts. Consequently, this paper describes how and why they brand themselves by using Apple products in their Instagram account. Personal branding theory related to impression management theory by Littlejohn and Computer-Mediated Communication (CMC) by Tomic describe these phenomena. The study employed qualitative descriptive methods by interviewing a young apple addict. The outcome of their use of apple products as personal branding is netizens’ favorable perception of social media. They believe that using Apple products will enhance their personal brand. Their personal branding will improve their relationships, friendships, existence, education, and careers, as well as their amusement and usefulness. In order to develop their personal brand, they utilized impression management by displaying an Apple product in a photo or video mirror selfie directly within their Instagram content.